Unfolding San Siro. antropologia, didattica sperimentale e spazio urbano - Pontiggia, Stefano (Antropologia Pubblica, 2024)
The contribution reflects on anthropology’s role in experimental educational courses aiming at investigating the urban. The contribution will describe an experimental educational experience to train architects, planners, and professionals involved in building inclusive cities for migrant populations. The course was blended in nature, partly online and partly through two intensive workshops of one week each in two marginal neighbourhoods in Milan and Berlin. The Milan workshop took place in the ERP neighbourhood of San Siro. It was based on a didactic device to elaborate alternative forms of narrative and intervention alternative to those that insist on the territory. In this distinctly interdisciplinary didactic context, the anthropological gaze can fruitfully interact with other knowledge at least two different levels. On the one hand, some of anthropology’s research techniques can be creatively applied to educational paths of studying the city. Walking, interviewing, observing, and stimulating the ethnographic relationship through performative events are some techniques implemented in the workshop. On the other hand, the anthropological gesture is also self-reflexive, implicated in the places in which it unfolds and building connections and comparisons between places and levels of analysis. In the specifics of the Milan workshop, these dimensions of anthropological gesture were translated into specific teaching tools with which students were confronted daily. The paper will critically examine the relationship between anthropology and urban-applied didactics. On the other hand, Practices of Urban Inclusion shows possible futures for the anthropological study of the city in terms of methods of inquiry and socialization of research data.